Experimental and numerical investigation of the cyclic response of stainless steel reinforced concrete columns - José Melo (2022)
Corrosion of carbon steel reinforcement is the major cause of premature deterioration of reinforced concrete infrastructures. There is increasing interest in the use of maintenance-free materials such as stainless steel reinforcement in concrete, with inherent durability and resistance to various forms of corrosion and favourable mechanical properties, in particular high ductility and substantial strain hardening. This paper presents the results of the first large-scale testing programme on reinforced concrete columns with duplex EN 1.4462 stainless steel rebars. Three cantilever column specimens were tested, two with EN 1.4462 stainless steel reinforcing bars, subjected to constant compressive axial load plus (i) monotonic loading and (ii) lateral cyclic loading, and one B500 carbon steel reinforced control specimen. In addition, conventional pull-out tests and tensile tests were conducted for a comparative assessment of the bond-slip behaviour and mechanical properties of the reinforcing bars. Numerical modelling simulations were carried out with the open-source finite element analysis platform OpenSees to predict the nonlinear response of stainless steel reinforced concrete columns and the results were compared with the measured experimental performance data. The force-displacement global responses and the dissipated energy evolutions of the tested columns from the experimental and numerical models are presented and compared.